The Effect of Commitment to Applying Governance Principles on Social Responsibility and Sustainable Performance in Small Enterprises after Corona Pandemic (Journal of Namibian Studies : History Politics Culture, 2023)
The study investigated to what extent the commitment to applying the principles of governance affects enhancing social responsibility and sustainable performance in small enterprises after the Corona pandemic. The problem of the study was represented in the changes in business environment, the financial crises and Corona pandemic crisis affected the sustainable performance of small enterprises. Financial irregularities also increased criticism of business management away from the social and ethical framework of business. The importance of the study lied in the importance of commitment to applying the principles of corporate governance in small enterprises and their role on achieving social responsibility and enhancing business ethics and quality of sustainable performance after the Corona pandemic. The study aimed to clarify to what extent applying the principles of governance affects enhancing social responsibility and quality of sustainable performance in small enterprises in the Kingdom of Saudi Arabia, and to explain to what extent applying the principles of governance affects enhancing business ethics and the quality of sustainable performance in small enterprises in the Kingdom of Saudi Arabia. The study verified the hypotheses: There is a statistically significant relationship between the commitment to applying the principles of governance and enhancing social responsibility and sustainable performance of small enterprises after Corona pandemic. There is a statistically significant relationship between the commitment to applying the principles of governance and business ethics in small enterprises after Corona pandemic. The researchers concluded the findings: There is a statistically significant relationship between the commitment to applying the principles of governance and enhancing social responsibility and sustainable performance of small enterprises after Corona pandemic. Governance contributes to managing and organizing the relationship between shareholders and quality of sustainable performance, contributes to selecting available ethical alternative and satisfies all stakeholders. Based on the findings the researchers recommend: Governance should be adopted because it increases performing social responsibility and right behavior, investing energies and gaining client’s and customer’s trust in product. Governance should be used as it achieves justice, equality and fair competition in community.